2022
DOI: 10.3390/life12111793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacological Rescue of Melanocortin-4 Receptor Nonsense Mutations by Aminoglycoside

Abstract: The melanocortin-4 receptor (MC4R) is critical for central satiety regulation, therefore presenting a potent target for pharmacological obesity treatment. Melanocortin-4 receptor mutations prevalently cause monogenetic obesity. A possibility of overcoming stop mutations is aminoglycoside-mediated translational readthrough. Promising results were achieved in COS-7 cells, but data for human cell systems are still missing, so uncertainty surrounds this potential treatment. In transfected HEK-293 cells, we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…In transfected HEK-293 cells, they tested whether translational bridging by the aminoglycoside geneticin in combination with the high-affinity ligand setmelanotide, which is effective in patients with proopiomelanocortin or leptin receptor deficiency, is a treatment option for affected patients. The authors concluded that N-terminal mutants were only slightly expressed regardless of treatment with geneticin, whereas mutants with nonsense mutations in transmembrane helix 6 or helix 8 showed wild-type-like expression [ 5 ].…”
mentioning
confidence: 99%
“…In transfected HEK-293 cells, they tested whether translational bridging by the aminoglycoside geneticin in combination with the high-affinity ligand setmelanotide, which is effective in patients with proopiomelanocortin or leptin receptor deficiency, is a treatment option for affected patients. The authors concluded that N-terminal mutants were only slightly expressed regardless of treatment with geneticin, whereas mutants with nonsense mutations in transmembrane helix 6 or helix 8 showed wild-type-like expression [ 5 ].…”
mentioning
confidence: 99%